2004
DOI: 10.1097/01.rli.0000129156.16054.30
|View full text |Cite
|
Sign up to set email alerts
|

Gd-BOPTA Transport Into Rat Hepatocytes: Pharmacokinetic Analysis of Dynamic Magnetic Resonance Images Using a Hollow-Fiber Bioreactor

Abstract: Rationale and Objectives:To investigate the transport of the hepatobiliary magnetic resonance (MR) imaging contrast agent Gd-BOPTA into rat hepatocytes. Materials and Methods:In a MR-compatible hollow-fiber bioreactor containing hepatocytes, MR signal intensity was measured over time during the perfusion of Gd-BOPTA. For comparison, the perfusion of an extracellular contrast agent (Gd-DTPA) was also studied. A compartmental pharmacokinetic model was developed to describe dynamic signal intensity-time curves. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 47 publications
(58 reference statements)
2
20
0
Order By: Relevance
“…In a similar experimental model, we previously showed by hepatic MRI that BSP totally abolishes the signal intensity enhancement induced by the coperfusion of BOPTA and BSP (Pastor et al, 2003). In isolated hepatocytes, we confirmed the cellular entry of BOPTA through a membrane transporter that is saturable at high substrate concentrations with a K m of 270 Ϯ 111 M and a V max value of 6.62 Ϯ 1.38 SI units at 30 min (Planchamp et al, 2004). Three Oatps have been described in rat livers: Oatp 1 , Oatp 2 , and Oapt 4 (Hagenbuch and Meier, 2003).…”
Section: Organic Anion Transport Within Hepatocytes Discussionsupporting
confidence: 63%
“…In a similar experimental model, we previously showed by hepatic MRI that BSP totally abolishes the signal intensity enhancement induced by the coperfusion of BOPTA and BSP (Pastor et al, 2003). In isolated hepatocytes, we confirmed the cellular entry of BOPTA through a membrane transporter that is saturable at high substrate concentrations with a K m of 270 Ϯ 111 M and a V max value of 6.62 Ϯ 1.38 SI units at 30 min (Planchamp et al, 2004). Three Oatps have been described in rat livers: Oatp 1 , Oatp 2 , and Oapt 4 (Hagenbuch and Meier, 2003).…”
Section: Organic Anion Transport Within Hepatocytes Discussionsupporting
confidence: 63%
“…In a hollow-fiber bioreactor containing freshly isolated rat hepatocytes, we showed that the transport of Gd-BOPTA into hepatocytes can be successfully described by compartmental analysis of the MR signal intensity recorded over time and supports the hypothesis of a transportermediated uptake (Planchamp et al, 2004a, b).…”
Section: Introductionsupporting
confidence: 70%
“…Moreover, we also demonstrated that the transport of Gd-BOPTA into isolated rat hepatocytes is saturable with a K m ϭ 0.3 mM. 3 In the literature, 3 transporters (Oatp1, Oatp2, and Oatp4) have been described on the sinusoidal (or plasmatic) membrane of rat hepatocytes, but the exact isoform responsible for Gd-BOPTA uptake is unknown. Following intracellular transport, Gd-BOPTA exits into bile through the ATP-dependent multidrug resistance-associated protein 2 (Mrp2, Abcc2).…”
mentioning
confidence: 99%